2005
DOI: 10.1007/s00417-005-0139-8
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane stents for lacrimal duct stenoses: 5-year results

Abstract: The long-term success rate of polyurethane stent implantation is very low (18.5%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…The systematic use of bicanalicular tubes is still controversial. Although some authors report better results with bicanalicular tubes when compared to no lacrimal intubation, with a success rate of 82% to 89% versus 67% to 75%, respectively, 3,4 many surgeons refrain from the systematic use of stents 16,28 or use them only in cases of presaccal stenosis. 16 Poor results, with a success rate of 18.5% to 31%, were published for a series using polyurethane stents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic use of bicanalicular tubes is still controversial. Although some authors report better results with bicanalicular tubes when compared to no lacrimal intubation, with a success rate of 82% to 89% versus 67% to 75%, respectively, 3,4 many surgeons refrain from the systematic use of stents 16,28 or use them only in cases of presaccal stenosis. 16 Poor results, with a success rate of 18.5% to 31%, were published for a series using polyurethane stents.…”
Section: Discussionmentioning
confidence: 99%
“…16 Poor results, with a success rate of 18.5% to 31%, were published for a series using polyurethane stents. 28,29 Silicone tubes with stainless steel probes on either end (BIKA, FCI, Groupe IOLTECH, Paris, France) were used in all of our patients. In the literature, removal of bicanal icular tubes was done within 1 to 6 months (average, 3 months).…”
Section: Discussionmentioning
confidence: 99%
“…Later, in 2005, Bertelmann and Rieck reviewed 92 patients who had undergone stent implantation, revealing that after a 5-year span, the long-term success rate was only 18.5%. Potential factors contributing to these poor long-term outcomes included stent surface structure, potential disruption of the lacrimal mucosa properties, stent design, induction of chronic inflammatory responses and the duration of stent placement [132]. Thus, both authors confirmed the unfavorable long-term viability of polyurethane.…”
Section: Biopolymers For Tear Duct Stents and Tubesmentioning
confidence: 72%
“…Outra complicação encontrada na literatura foi perda visual permanente, devido a um quadro de celulite orbitária e neuropatia óptica isquêmica, quatro dias após o implante (13) . Atualmente há três estudos multicêntricos publicados que avaliam a taxa de sucesso a médio e longo prazo, sendo dois deles com seguimento de cinco anos (14)(15) , e o outro com acompanhamento aproximadamente de 24 meses (3) . No iní-cio, a colocação do implante de ducto nasolacrimal melhora os sintomas de epífora em 70-100% dos casos, porém as taxas de recorrência da obstrução da via lacrimal podem chegar a 30% no primeiro ano (11) .…”
Section: Discussionunclassified
“…Este mesmo estudo descreve a necessidade de novo procedimento para os pacientes que permaneceram com epífora após o implante. Destes, 28,9% foram submetidos à dacriocistorrinostomia externa e retirada do implante, 13,2% a extração via endoscópica transnasal, e 47,4% não receberam tratamento apesar do sintoma (14) . As complicações a longo prazo podem ser relacionadas a várias circunstâncias, tais como a estrutura do implante (o material nitinol tem piores resultados comparados ao poliuretano), o desenho do implante, a indução da resposta inflamatória, e o tempo de permanência na via lacrimal.…”
Section: Discussionunclassified